Feeding Practices of Infants and Young Children in Pokhara Metropolitan City - Manandhar, Varsha; Upadhyaya, Baidehi; Manandhar, Smriti; Manandhar, Alisha; Ghimire, Amrita (Journal of Nepal Health Research Council, 2024)
Background: For children to grow and develop normally, appropriate feeding practices are essential, especially in the first two years of their lives. These practices can vary depending on the different sociodemographic factors. This study aims to study the feeding practices of infants and young children in different wards of Pokhara Metropolitan City.Methods: A community-based cross-sectional study was conducted and 280 mothers of infants and young children 0-23 months of age were interviewed using a semi-structured questionnaire. Data were entered and cleaned in Ms-Excel and then exported to SPSS version 21.0 for statistical analysis. Binary logistic regression analysis was used to find the association of feeding practices with different independent variables.Results: Only 32.3% of children 0-5 months of age were found to be appropriately breastfed, and 41.8% of children 6-23 months of age were found to have appropriate complementary feeding practices. Children delivered by normal vaginal delivery (AOR 18.118, p < 0.01, 95% CI 3.831 – 85.689) were more likely to have appropriate breastfeeding practices than those delivered by caesarean section. Children of birth order two or more (AOR 2.226, p = 0.016, 95% CI 1.171 – 4.620) and living in nuclear families (AOR 2.488, p = 0.013, 95% CI 1.120 – 5.116) were found to have appropriate complementary feeding practices.Conclusions: This study concludes that the feeding practices of the majority of the infants and young children in Pokhara are not adequate as per the WHO and UNICEF standards.Keywords: Breastfeeding; complementary feeding; IYCF; Pokhara.